PERBEDAAN PERSEPSI ETIS DOSEN AKUNTANSI TERHADAP PRAKTIK EARNINGS MANAGEMENT DI KOTA PEKANBARU DALAM PERSPEKTIF GENDER - Khairil Henry (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
Earnings management is an action that may mislead users of financial statements by presenting inaccurate information, and sometimes even the cause of the illegal act. Some empirical evidence suggests that the company is actively practicing earnings management. The practice of earnings management is a form of attention to ethical issues and so need to be introduced to curriculumdevelopment, because the practice of earnings management assessed ethically ambiguous. This study tried to see if there are differences in ethical perceptions of accounting faculty to earnings management practices in terms of the type of manipulation, the manipulation direction, materiality and intention of earnings management by gender. The population is accounting lecturer at several universities in Pekanbaru taken by purposive sampling. Data collection method used by distributing questionnaires and if normally distributed data then test the hypothesis 1 (H1) was performed using parametric statistical analysis tools is by using independent sample T test (different test for two independent samples/free). The results of this study showed, although there is no significant difference between the accounting faculty of men and women in ethical perception of earnings management, but more women accounting faculty have high ethical orientation or inclination not accept the practice of earnings management compared with man accounting lecturer.